Praktik Integrasi Pembelajaran, Bermain, dan Pengasuhan Responsif dalam Layanan Daycare Terintegrasi Kota Serang - Ayu Fajarwati; Siti Khosiah (JEA (Jurnal Edukasi AUD), 2026)
Daycare is no longer understood merely as a child-minding facility but also as an early childhood education and care environment that supports children’s learning, play, rest, and emotional well-being. This study aims to describe the integration of learning, play, and responsive care in integrated daycare services in Serang City, Banten Province. This research employs a descriptive qualitative approach. Data were collected through non-participant observation, semi-structured interviews, and documentation involving five key informants: one daycare centre manager, two teachers, and two caregivers. Observations were conducted on the daily activities of 12 children aged 3-6 years. Data were analysed using thematic coding through the stages of data reduction, data display, and conclusion drawing. Data validity was ensured through source triangulation and methodological triangulation. The research findings indicate that learning takes place in the morning through a centre-based learning model, whilst activities during daycare hours are conducted at a lighter intensity through structured play, free play, rest, and care routines. Responsive care is evident in the carers’ sensitivity to the children’s physical and emotional states. These findings confirm that the quality of integrated daycare is determined by a balance between learning play, rest, and responsive care practices.